PENGARUH UPAH MINIMUM PROVINSI DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP TINGKAT PENGANGGURAN PROVINSI ACEH - Angga Angga; Fikriah Fikriah (Fakultas Ekonomi dan Bisnis UNSYIAH, 2020)
AbstractThis study aims to analyze the influence of minimum wage and human development index on unemployment rate in Aceh Province. The variables used in this study are province minimum wage,human development index, and variable unemployment rate. The data used in this study is time series in the period 2004-2018 and analysis model used is multiple linear regression. The results of this study indicate that the UMP variable has a positive and significant effect on employment rate, while the H0, variable has a negative and not significant to unemployment rate,but on the coeficient determinant (R2), both variables has significant effect on unemployment. The results of this study are to be an indicator of the the Aceh’s government in choosing politicies that are appropiate to reduce unemployment and to increase job vacancy for unemployed in various sector.Keywords: Unemployment. Human development index. Minimum wage